Workplace bullying in Malaysia: an exploratory study - Al Bir, Ahmed Talib Sadiq; Hassan, Arif (Malaysian Institute of Management, 2014)
This paper aims at investigating the prevalence of workplace bullying and the frequency of its negative acts in Malaysia. Bullying in the workplace was measured using the Negative Acts Questionnaire (NAQ-R) developed by Einarsen et al (2003). A sample of 231 randomly selected respondents participated in the study. They represented both the public and private sectors, and several industry and job levels. The frequency of the negative acts (now and then, monthly, weekly, daily), excluding never, revealed shocking numbers. Among the different forms of bullying, the results indicated that 81.4% were being bullied by someone withholding information that affected their performance, 82.2% were being bullied by someone spreading gossip about them, and 82.3% were being bullied by being given tasks with unreasonable deadlines.